Analisis Komparasi Kebijakan Fiskal Masa Umawiyah, Abbasiyah, Umawiyah Di Spanyol dan Kerajaan Kecil - Sobarna, Nanang; Janwari, Yadi; Al-Hakim, Sofyan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Fiscal policy had an important role in shaping the economic and social stability of society during the era of the Islamic Caliphate, starting from the Umawiyah and Abbasiyah periods, the Umawiyah in Spain to the Small Kingdoms. Fiscal policy during these times not only functions to collect revenue but also to support development, social welfare, and maintain political stability. This research aims to analyze the history of fiscal policy in various periods by highlighting the main sources of income, allocation of fiscal funds, and the effectiveness and benefits of policies in supporting economic development. This research approach uses a historical descriptive method by analyzing primary and secondary literature sources. The data collected includes aspects of fiscal policy such as the type and amount of taxes applied, financial administration systems, and budget distribution in various public sectors. The analysis is carried out comparatively to highlight the differences and similarities between fiscal policies during the times of large caliphates and small kingdoms in meeting the social and economic needs of society. The research results show that fiscal policy during the Umawiyah and Abbasiyah periods tended to rely on sources of income from agricultural taxes (kharaj), taxes on non-Muslims (jizyah), zakat, and trade taxes (usyr). During the Umawiyah period in Spain, fiscal policy succeeded in creating harmonious social and economic integration between Muslim and non-Muslim communities, thanks to fair tax policies and investment in community welfare.